Synthesis and Characterization of High‐Entropy CrMoNbTaVW Thin Films Using High‐Throughput Methods. Issue 2 (19th January 2023) - Schweidler, Simon; Schopmans, Henrik; Reiser, Patrick; Boltynjuk, Evgeniy; Olaya, Jhon Jairo; Singaraju, Surya Abhishek; Fischer, Franz; Hahn, Horst; Friederich, Pascal; Velasco, Leonardo
Abstract : Using an optimized high‐throughput magnetron sputtering synthesis, a new high‐entropy alloy (HEA) gradient film consisting of CrMoNbTaVW is synthesized by Simon Schweidler, Pascal Friederich, Leonardo Velasco, and co‐workers in the article number 2200870 . The compositional space of the HEA system is studied in different subsections to determine the influence of the individual elements and their combinations, as well as the structure, morphology and physical properties (hardness and resistivity).